The simulation of ELM control by the advanced divertor configuration in EAST - Y.L. Li; T.Y. Xia; Z.P. Luo; Q.Z. Yu; S.F. Mao; B. Gui; X.X. He; H.M. Qi; P.C. Xie; M.Y. Ye; the EAST team (Nuclear Fusion)
Edge localized modes (ELMs) are effectively suppressed in the ‘quasi-snowflake’ (QSF) divertor discharges, which has been observed in the Experimental Advanced Superconducting Tokamak (EAST). To obtain the physical mechanism of ELM suppression, the numerical simulations are carried out using the BOUT++ turbulence model. The simulations reveal that the large local magnetic shear near the outer mid-plane (OMP) induced by QSF divertor plays a key role in the ELM suppression. Using the EFIT code, a series of plasma equilibria with different 2nd X-points and nearly fixed last closed flux surfaces (LCFSs) are generated to analyze the effects of the different magnetic configurations on ELMs. Here we mainly discuss the standard single-null (SN), snowflake plus (SF+), and snowflake minus (SF-) divertors. The simulation results indicate that: (1) for linear instability, compared to SN, SF+ is more unstable, while SF- is more stable. Essentially, the local magnetic shear formed by different divertor geometries can alter the growth rate of the peeling-ballooning (P-B) mode. Through statistical analysis, there is an inverse correlation between the strength of local magnetic shear and the growth rate of P-B mode; (2) for ELM energy loss, SN is 4.60%, SF+ is 7.50%, and SF- is 0.35%. The SF+ divertor triggers a larger ELM, which is consistent with the TCV experiments; while the SF- divertor reduces the ELM amplitude, which is similar to the QSF experiments in EAST. Further analysis shows that the Reynolds stress determines the ELM size under different divertor configurations. The Reynolds stress can redistribute energy to fluctuations and cause the growth of low- n modes. What’s more, the SF- divertor not only suppresses the radial transport, but also has large magnetic flux expansion and connection length, which can reduce the target heat flux effectively. The conclusion of this paper shows that the advanced divertor configurations are promising for the future fusion.